2019
DOI: 10.1186/s13065-019-0517-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-aminobenzamid@Al-SBA-15: a favorable catalyst in synthesis of 2,3-dihydroquinazolin-4(1H)-ones

Abstract: The novel hybrid Co-aminobenzamid@Al-SBA-15 was synthesized as a modified mesoporous catalyst. To achieve this aim, the obtained materials were investigated by various techniques including Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), N 2 adsorption–desorption, field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM) to examine the functional groups, crystallinity, surface area, morphology, particle size distribution and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…To now, several methods have been reported for the one-pot multi-component condensation synthesis of acridine and quinazoline derivatives, 41 employing a wide variety of catalysts such as Fe 3 O 4 /HT-SMTU-Zn II , 42 SBA/AuNP, 43 [Nbdm][OH], 44 Co-aminobenzamid@Al-SBA-15, 45 α-chymotrypsin, 46 Pd(OAc) 2 , 47 KCC-1/Pr-SO 3 H, 48 and CuCl 2 , 49 Co–alanine complex, 50 magnetic praseodymium nanocatalyst, 51 nano-Fe 3 O 4 -DOPA-SnO 2 , 52 MNPs-NPB-SO 3 H, 53 SDS 54 and bentonite. 55 Despite the usefulness of these catalysts, they also have some limitations including high toxicity, use of expensive materials, complex synthetic processes, long reaction times, and sometimes low yields.…”
Section: Introductionmentioning
confidence: 99%
“…To now, several methods have been reported for the one-pot multi-component condensation synthesis of acridine and quinazoline derivatives, 41 employing a wide variety of catalysts such as Fe 3 O 4 /HT-SMTU-Zn II , 42 SBA/AuNP, 43 [Nbdm][OH], 44 Co-aminobenzamid@Al-SBA-15, 45 α-chymotrypsin, 46 Pd(OAc) 2 , 47 KCC-1/Pr-SO 3 H, 48 and CuCl 2 , 49 Co–alanine complex, 50 magnetic praseodymium nanocatalyst, 51 nano-Fe 3 O 4 -DOPA-SnO 2 , 52 MNPs-NPB-SO 3 H, 53 SDS 54 and bentonite. 55 Despite the usefulness of these catalysts, they also have some limitations including high toxicity, use of expensive materials, complex synthetic processes, long reaction times, and sometimes low yields.…”
Section: Introductionmentioning
confidence: 99%
“…3a) in the range of 0.9-2, is agreeable with the reported XRD of mesoporous compounds in the literature. [24][25][26][27][28] Due to the high-angle X-ray diffraction (Fig. 3b), there is a wide peak at an angle between 15 and 30, which is attributed to the structure of the mesoporous material.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 Safaei Ghomi et al reported several of supported SBA-15 catalysts. Generally, in these reported works, the SBA-15 mesoporous silica was employed as a support metal species, and a highly dispersed metal catalyst was utilized in different multicomponent reactions, [31][32][33] for example, they prepared functionalized-SBA-15 using a tetradentate ligand to construct a new catalyst. They investigated the efficiency of this catalyst in the synthesis of 2-azapyrrolizidine alkaloids, which have different biological properties.…”
Section: Introductionmentioning
confidence: 99%